Combined use of UV-C irradiation and heat treatment to improve postharvest life of strawberry fruit - Pan, Jeronimo (2004)
The effects of UV-C (4.1 kJm−2) and heat treatment (45 ◦C, 3 h in air) either separately or combined on the quality of strawberries (Fragaria × ananassa cv Seascape) at the 75 or 50% surface red ripening stage were assessed, the latter stage being used only in the firmness test. In addition, the development of surface fungal infections was followed and in vitro germination assays on conidia of Botrytis cinerea and Rhizopus stolonifer performed. Both heat and combined treatments, decreased hue and delayed changes of the L∗ parameter. All treatments reduced the accumulation of anthocyanins. Control fruit softened most while fruit treated by the combined method were the firmest. The combined treatment reduced fungal infections and delayed in vitro germination of Botrytis cinerea conidia. After 2days at 20◦C, treated fruit had lower amount of phenolics than the control. Neither the heat nor UV-C irradiationmodified the total sugar content, although the combined treatment decreased it slightly relative to the control. Titratable acidity increased through storage at 20 ◦C in all fruit, but no differences between control and treated fruit were detected. The combination of UV-C and heat treatments enhanced the benefits of applying each treatment separately, and could be useful to improve and extend strawberry fruit postharvest life.